PROFITABILITAS DAN LEVERAGE PENGARUHNYA TERHADAP MANAJEMEN LABA PADA PERUSAHAAN DAGANG - MUHAMMAD ASMUNANDAR; FRIYANTO (Pusat Publikasi dan Penerbitan Karya Ilmiah STIE Indonesia Malang, 2022)
The purpose of this study is to determine the profitability and leverage partially or simultaneously which have a significant effect on earnings management in trading companies listed on the Indonesia Stock Exchange. The population determined is as many as 70 trading companies listed on the Indonesia Stock Exchange. Sampling was done by purposive sampling method. A total of 10 companies that meet the criteria as a sample in this study. The period of observation in this study is 2017-2019. The method used to analyze the data is multiple linear regression analysis, F test, and t test. The results of the study prove that profitability has no significant effect on earnings management in trading companies listed on the Indonesia Stock Exchange for the 2017-2019 period. Leverage has a significant negative effect on earnings management in trading companies listed on the Indonesia Stock Exchange for the 2017-2019 period. The results showed that the profitability and leverage variables simultaneously had no significant effect on earnings management in trading companies listed on the Indonesia Stock Exchange for the 2017-2019 period.